Public Spending Efficiency in the OECD Benchmarking Health Care, Education and General Administration - Dutu, Richard (OECD Publishing, 2016)
In many OECD countries changes in demography and health conditions are putting pressure on public finance. To prevent further expansion of government spending as a percentage of GDP, public spending efficiency will need to be raised. This paper uses data envelopment analysis (DEA) to assess the efficiency of welfare spending in a sample of OECD countries around 2012, focussing on health care, secondary education and general public services. The DEA model has a two input-one output structure, with at least one of the variables representing a composite indicator controlling for country-specific factors (socio-economic environment and life-style factors, for example). We find wide dispersion in efficiency measures across OECD countries and provide possible quantified improvements for both output and input efficiency
Keywords: Social Issues/Migration/Health; Economics